A Novel Photo-Driven Hydrogenation Reaction of an NAD+-Type Complex Toward Artificial Photosynthesis - Ohtsu, Hideki; Saito, Tsubasa; Tsuge, Kiyoshi (Frontiers in Chemistry, 2019)
The photocatalytic reduction of carbon dioxide (CO2) to value-added chemicals is an attractive strategy to utilize CO2 as a feedstock for storing renewable energy, such as solar energy, in chemical bonds. Inspired by the biological function of the nicotinamide adenine dinucleotide redox couple (NAD+/NADH), we have been developing transition-metal complexes containing NAD+/NADH-functionalized ligands to create electro- and/or photochemically renewable hydride donors for the conversion of CO2 into value-added chemicals. Our previous findings have provided insights for the development of photocatalytic organic hydride reduction reactions for CO2, however, further examples, as well as investigation, of these photo-driven NAD+/NADH-type hydrogenation and organic hydride transfer reactions are required not only to explore the mechanism in detail but also to develop a highly efficient catalyst for artificial photosynthesis. In this paper, we report the synthesis, characterization, and photo-induced NAD+/NADH conversion properties of a new ruthenium(II) complex, [Ru(bpy)2(Me-pn)](PF6)2 (1), which contains a new NAD+-type ligand, Me-pn (2-methyl-6-(pyridin-2-yl)-1,5-naphthyridine). In addition, we have succeeded in the isolation of the corresponding two-electron reduced ruthenium(II) complex containing the NADH-type ligand Me-pnHH (2-methyl-6-(pyridin-2-yl)-1,4-dihydro-1,5-naphthyridine), i.e., [Ru(bpy)2(Me-pnHH)](PF6)2 (1HH), by the photo-induced hydrogenation reaction of 1. Thus, in this study, a new photo-driven NAD+/NADH-type hydrogenation reaction for possible CO2 reduction using the NAD+/NADH redox function has been constructed.